Qualitative assessment of progressive addition lenses (PALs) prescription / Rabiatun Mujari - Mujari, Rabiatun (Faculty of Health Sciences, 2015)
Introduction: Progressive additional lenses (PALs) are increasingly preferred mode for the correction of presbyopia. The objectives of this study were to determine PALs wearer perceived quality of vision as total satisfaction and to assessed the correlation of quality of vision and symptoms reported with total satisfaction level of PALs delivered by UiTM Vision Care. Material and methods : This study was a cross sectional survey. Thirty-two respondents from target population were recruited respectively. A self-administered questionnaire was given to respondents. The questionnaires was adopted from The Ohio State University to evaluate the satisfaction level of visual performance using the in the respondent‟s daily living activities. The quality of vision includes the questions regarding distance viewing, intermediate viewing, near viewing and mobility. Each question was scored based on a Likert scale ranging from 0 to 10. Results : Result showed there was high positive and significant correlation in all quality of vision with total satisfaction as well as the symptoms reported among PALs wearers with total satisfaction. The highest significant correlation was found in intermediate viewing which seeing computer screen and seeing grocery shelves. Blurred vision showed lowest correlation among other symptoms reported. Slopes of the regression lines for each task are positive. For the correlation of symptoms reported with total satisfaction, results showed high correlation of symptoms reported with total satisfaction. Results showed no significant differences between the symptoms indicates PALs wearer able to adapt and can use PALs without any significant visual problems in their daily activities. Conclusion : In conclusion, most of PALs wearer dispensed by UiTM Vision Care showed high level of satisfaction with the PALs dispensed and experienced less symptoms associated with the PALs. PALs wearers can easily adapt to and use PALs without significant visual problems during daily activities.